Immunosenescence and Inflammaging in Dogs and Cats: A Narrative Review - Brennen A. McKenzie (Journal of Veterinary Internal Medicine)
ABSTRACT A consistent and important feature of biological aging is the change in the types and functions of cells comprising the immune system. Across various mammalian species, this change follows consistent patterns, including diminished protective capacity, leading to increased vulnerability to infectious disease, and increased low‐grade chronic inflammation, raising the risk of numerous aging‐associated diseases. Although these patterns are well characterized in rodents and humans, there is less evidence available in companion animal species. The most recent review of the literature evaluating aging changes in the immune system in dogs and cats was published in 2010. The purpose of this narrative review is to summarize the currently available information concerning immune system aging in these species and to review what is known about the clinical consequences of this process and about potential strategies for mitigation.